Strategi Manajemen Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Kinerja Pendidik di SMK Madyatama Palembang - Isnaini Indah Mutmainah; Tri Widayatsih; Muhammad Fahmi (STKIP Pesisir Selatan, 2024)
Education requires a principal's strategy to improve the quality of services so that the focus is directed at teachers and other education personnel so that the education management they lead can run well. The purpose of this research is to explain the principal's leadership management strategy in improving the quality of educators at SMK Madyatama Palembang. The method used in this research is descriptive using a qualitative approach. The results of this study the principal did a way to improve the quality of educators by giving awards in the form of certificates for teachers who came on time, and held training or training held from outside on the recommendation of the principal and conducted supervision once a year, the principal's leadership management strategy in improving the quality of educators at SMK Madyatama Palembang by providing motivation in the development of human resources in SMK Madyatama, increasing discipline, the principal coordinates with related parties in developing and improving the quality of educators and giving freedom to each educator to develop the quality of his potential by attending training recommended by the principal.